Método de posicionamento estratégico de serviços para uma concessionária de distribuição de energia elátrica - Correa, Geison Cris (Universidade do Vale do Rio do Sinos, 2008)
The changes occurred in the Brazilian electric sector and the sophistication of consumer market have demanded, throughout time, services with quality standards increasingly more and more. This segment, which before structural reforms was characterized by large state and monopolist conglomerates, currently is composed by private, state and regional cooperative enterprises, placed in a new competitive environment. Therewith, the concessionaries need to reach excellence in service management to enable the desired financial return associated with the fulfillment of regulatory requirements. The proposition of a strategic positioning method based on the Strategic Positioning Matrix of Materials (MPES) allows the segmentation in the supply applied to the scope of services, it supports the planning of strategic actions in the supply chain (as much verticalized as outsourced), and, moreover, it enables the development of qualifying criteria for the choice of suppliers. This work was developed in three stages. The firs
Keywords: concessionárias de energia elétrica; vantagem competitiva; estratégia; competitive advantage; concessionaires of electric energy; strategy; Engenharias